"For the true benefit of the human family": Sociological and ethical analysis on a document on human fraternity for world peace and living together - Biały, Stanisław (Prawo Kanoniczne, 2020)
This article is an attempt to evaluate, in the ethical and sociological way, the event of signing the Document on Human Fraternity for World Peace and Living Together in the capital of the United Arab Emirates Abu Dhabi (Zabi) on February 4, 2019 by Pope Francis and the Grand Imam of the Islamic Al-Azhar University in Cairo, Sheikh Al-Azhar Ahmad Al-Tayyeb. This act took place at a conference devoted to human fraternity organized by the Muslim Council of Elders, founded in 2014, aimed at overcoming divisions and feuds within Islam, as well as defending this religion against extremists, and promoting the message of human values and tolerance. This document - signed in the context of the assumed goals of the association, as well as the problems of various current religious conflicts (not excluding acts of terrorism) - can be considered an epochal act. It is (in a sense) the culmination of the theological reflections and actions of the predecessor of Pope Francis - Benedict XVI, who, in his significant speech at the University of Ratysbon (March 6, 2006), very boldly described the ethical and theological misunderstanding of usurpation of the law ( in the name of God) to spread one’s religion also with violence, and, what Muslims call, jihad. He stated that violence is an irrational thing and that, as such, it cannot correspond to the rational (and holy) nature of the God we believe in. The protests, which appeared in the Muslim world then, today, with the act of signing this document, seem to be just an echo of unnecessary misunderstanding between the two great religions. Thus, the author of the article comes to the conclusion that one should hope that this document will bring peace in the world and establish positive relations between Christians and Muslims. Moreover, he believes that a great respect for the signatories of such an important reciprocal declaration should be expressed. However, he points out that the document (as important as it is) will not automatically improve the relations between the warring parties, nor will it change the thinking of the people we call fundamentalists (radicals). There is a need for further mutual work and contact for the benefit of even better understanding and reconciliation.